New Continuous Barbed Suture Device with Stratafix for the Vaginal Stump in Laparoscopic Hysterectomy - Yanazume, Shintaro (Gynecol Minim Invasive Ther, 2018)
AIMS: Closure of the vaginal stump in total laparoscopic hysterectomy (TLH) performed by interrupted suture is time-consuming and requires sufficient experience. Stratafix (SF) is a new type of antibacterial monofilament absorbable suture which has multiple small anchors on the string surface. There is no information concerning the efficacy of SF for vaginal stump suture in minimally invasive hysterectomy. MATERIALS AND METHODS: We retrospectively evaluated the operative complications and SF (n = 20) advantages for the vaginal stump in TLH and compared with a cohort of patients with conventional sutures (n = 20). The differences in performance based on operators’ skill levels were also considered. RESULTS: The time taken to close vaginal stump in the SF suture group was significantly lower than the conventional group (median times: 13.1 vs. 18.0 min, respectively; P = 0.038). Closure by a less experienced operator using SF suture was reduced by 7.2 min. The junior operator median vaginal suture time was only 2.6 min longer than the senior operator median time in SF suture group (P = 0.218), whereas an 8.4 min difference was recorded in the conventional suture group (P = 0.043). Total operation times did not significantly correlate with vaginal suturing techniques (median times: 126 vs. 145 min, respectively; P = 0.718). Complications regarding the vaginal stump closure techniques including organ injury, bleeding, wound separation, and pain did not occur in both groups. CONCLUSIONS: SF suturing facilitates the vaginal stump closure in TLH without increasing the complications. SF allowed vaginal stump approximation and reduced the operative burden, especially in less experienced operators.